Environmentally stable interface of layered oxide cathodes for sodium-ion batteries - Shaohua Guo (Nature Portfolio, 2017)
The interface of layered cathodes for sodium ion batteries is subject to atmospheric and electrochemical corrosions. Here, the authors demonstrate an environmentally stable interface via titanium enriched surface reconstruction in a layered manganese-based oxide.